Immunogenic evaluation of LptD + LtgC as a bivalent vaccine candidate against Neisseria gonorrhoeae - Narjes Noori Goodarzi; Seyed Mahmoud Barzi; Soheila Ajdary; Mohsen Chiani; Mir Saeed Yekaninejad; Farzad Badmasti; Mohammad Reza Pourmand (Journal of Translational Medicine)
Abstract Background Neisseria gonorrhoeae is an escalating global health threat due to increasing antimicrobial resistance. The emergence of multidrug-resistant (MDR) strains necessitates alternative prevention strategies. This study focused on the development of a bivalent vaccine formulation to address this challenge. Lipopolysaccharide transport protein D (LptD) and lytic transglycosylase C (LtgC) as two promising immunogenic targets were considered in this study. Methods The ltgC and lptD genes of N. gonorrhoeae ATCC 19424 were amplified, then cloned into the pET-28a (+) vector, expressed in Escherichia coli BL21 (DE3), and purified using Ni-NTA affinity chromatography. Antigen-specific total IgG levels in serum of patients with gonorrhea were assessed using enzyme-linked immunosorbent assay (ELISA). Proteins were formulated with monophosphoryl lipid A (MPLA) adjuvant in three groups: LptD, LtgC, and a bivalent LptD + LtgC. One additional group received LptD with liposomal MPLA, along with control groups. Vaccine formulations were administered to BALB/c mice in three doses at two-week intervals. Total IgG, IgG1, IgG2a, and IgA levels in sera and vaginal samples were measured using ELISA. Moreover, serum bactericidal (SBA) and opsonophagocytic (OPA) assays were conducted. Results The total IgG levels against both proteins were considerably higher in the patients’ sera compared to healthy individuals. All vaccine formulations significantly increased total IgG levels in animal model. The LptD + liposomal MPLA group exhibited the highest specific IgG level, whereas the bivalent formulation group exhibited the highest long-term IgG level until the day 112, which also yielded the strongest total IgG response in the whole-cell ELISA. The IgG2a/ IgG1 ratio was greater than 1 in all vaccine regimens, indicating a Th1-polarized response. The LptD + liposomal MPLA formulation elicited the highest serum IgA levels, followed by the LptD + LtgC combination. In addition, the bivalent formulation achieved the highest SBA and OPA titers. Conclusion This study successfully developed and evaluated a recombinant bivalent vaccine against N. gonorrhoeae. This formulation exhibited the most potent immunogenicity, as evidenced by higher antibody levels and SBA and OPA titers than single-antigen formulations. The Th1-polarized immune response further highlights the vaccine’s potential to elicit a protective immune profile. These findings suggest that this multi-antigen formulation can be a promising vaccine candidate against gonorrhea. However, more investigations are required to confirm the vaccine efficacy.